SPATIAL ANALYSIS OF RELATIONSHIP BETWEEN COVID-19 CASES AND GLOBALISATION IN EUROPE - Yılmaz Toktaş (Polityki Europejskie, Finanse i Marketing)
With the globalisation process, economic, social and political structures have become more and more intertwined. Due to the current Covid-19 pandemic, it has been observed that epidemics such as Covid-19 are globalising and that they turn into pandemics on a global scale. In this study, it is suggested that, along with Covid-19’s distinctive abilities such as spreading rapidly, the fact that the world has become more mobile and integrated due to globalisation is considered to have an impact on the pandemic; thus, the effect of globalisation on Covid-19 cases in European countries was investigated through spatial analysis methods. The results of Moran’s I test carried out on Covid-19 cases in European countries suggest that there is positive autocorrelation. According to the LISA analysis results, it was found that the UK, the Netherlands, France, and Belgium not only have a higher number of Covid-19 cases, but also have been affected by the countries with a number of cases above the European mean. According to the results of Spatial Error Model designed to examine the effect of globalisation, it was found that globalisation had a slight but positive effect on Covid-19 cases in Europe.